1983
DOI: 10.1111/j.1600-0722.1983.tb00845.x
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus mutans establishment and dental caries experience in children from 2 to 4 years old

Abstract: – 39 children were studied longitudinally at the age of 2, 3, and 4 yr for the colonization of S. mutans in plaque and saliva and for caries experience. S. mutans was found in 38% of the children, and the predominant serotype group was c/e/f. A total of 16 children got caries before the age of 4. Children who harbored S. mutans in their plaque at the age of 2, appeared to be the most caries‐active individuals. Their caries index values (number of decayed, missed and filled surfaces, dmfs = 10.6±5.3) at the ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
188
2
42

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(258 citation statements)
references
References 19 publications
26
188
2
42
Order By: Relevance
“…These findings reinforce the multifactorial etiology of caries, where the joint action of several etiological factors is needed, that is, a cariogenic diet, poor oral hygiene, susceptible host and Streptococcus mutans oral infection: together they create an environment that promotes the development of carious lesions (7)(8)(9)(10) . Regarding healthy habits and oral health risk, we observed that children in Argentina do not have oral hygiene habits, and there was a significant difference with the Brazilian cohort.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…These findings reinforce the multifactorial etiology of caries, where the joint action of several etiological factors is needed, that is, a cariogenic diet, poor oral hygiene, susceptible host and Streptococcus mutans oral infection: together they create an environment that promotes the development of carious lesions (7)(8)(9)(10) . Regarding healthy habits and oral health risk, we observed that children in Argentina do not have oral hygiene habits, and there was a significant difference with the Brazilian cohort.…”
Section: Discussionsupporting
confidence: 63%
“…Studies conducted by Adair et al (3) have shown the influence carbohydrates, especially sugars, have on the occurrence of carious lesions. Poor eating habits, such as the intake of sugary substances in the baby's bottle, are closely tied to early Streptococcus mutans colonization, one of the main cariogenic bacteria in the oral cavity (7)(8)(9)(10) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…É sabido que quanto mais precocemente ocorrer a infecção na dentição decídua da criança, por microrganismos patogênicos, maior a prevalência de cárie nessa dentição 1,14 . Hábitos arraigados no cotidiano do cuidado infantil, como provar os alimentos com a colher da criança, ou resfriá-los soprando, são as principais formas de transmissão da infecção da mãe para o filho 1 .…”
Section: Introductionunclassified
“…Hábitos arraigados no cotidiano do cuidado infantil, como provar os alimentos com a colher da criança, ou resfriá-los soprando, são as principais formas de transmissão da infecção da mãe para o filho 1 .…”
Section: Introductionunclassified